Determinants of Nurse Compliance in Fall Risk Screening: A Study At X Hospital Pekanbaru - Khairiyah, Oktarisa; Shaluhiyah, Zahroh; Purnami, Cahya Tri (Research and Community Service Unit, Poltekkes Kemenkes Kupang, 2024)
Patient safety is a system that aims to make health services safer, preventing injuries due to errors in carrying out actions or not taking actions that should be taken, by using risk screening for patients. This research was conducted to see the effect of nurses' compliance in completing the complete patient fall risk screening at Hospital X Pekanbaru. This research was a descriptive analytical study with a cross-sectional approach carried out at Hospital X Pekanbaru, using a sample of 133 nurses at Hospital X Pekanbaru. Data was collected using questionnaires and interviews regarding nurses' compliance in filling out the patient fall screening sheet using a Likert scale questionnaire. Several variables were included in the analysis, including age, gender, highest level of education, length of service, work shifts, workload, rewards, knowledge, supervision, attitudes and compliance with the implementation of fall risk screening. All variables are converted into categorical data (nominal or ordinal). The analysis in this study was univariate analysis (frequency and percentage) and bivariate analysis was carried out using the Chi-Square Test statistical method with a p value <0.05. The results showed that length of service had an effect on nurses' compliance in completing the fall risk screening (p = 0.049). However, there is a tendency that those aged <31 years are more likely to be non-compliant, while those aged >31 years are more likely to be compliant in completing the screening requirements. Meanwhile, it was also found that nurses with a working period of <6 years were more likely to be non-compliant, while those with a working period of >6 years were more likely to be compliant in filling out the screening requirements, so it was found that compliance with completing the patient fall risk screening by nurses would increase by 2. 1 time.